Impact of the internet on the travel industry in Singapore. - Goh, Junfeng. (2008)
The Internet has changed the way travel businesses operate dramatically. Websites serve not only as powerful means of information distribution but also provide e-commerce for travel organizations. Today, travel companies can sell their products direct to consumers all over the world online. However, this phenomenon is also a threat to travel intermediaries, who may become obsolete in the near future. In the light of the e-revolutionizing travel industry, this research sought to provide valuable insights on both travel organizations’ and consumers’ perspectives on the changing landscape of the travel industry in Singapore. Specifically, the research sought to identify business attitudes and beliefs held by successful travel organizations. A simple consumer survey was included to discover if these attitudes and beliefs were reinforced from the consumer perspective. This two-pronged approach will reveal the impacts the Internet had on Singapore’s travel industry. Our company case studies showed a consensus that the Internet was a popular, effective and low cost method for information broadcast which also increased the business potential for the companies. The consumer surveys findings reiterated the case studies on these points. However, the Internet also increased the risk for certain companies as consumers could now purchase direct from suppliers. Other problems were increased work due to a need for frequent website updates and the increased need to pacify consumer fears regarding security issues. Interestingly, the consumer survey revealed that websites were not able to provide certain features consumers valued, such as personal advice, or making the purchase largely hassle free, without a need for lengthy administrative procedures. The Internet will continue to have a major stake in the travel industry. As the Internet continues to grow in popularity, online markets expand. The Internet is the opportunity for Singaporean travel companies to reach out to the rest of the world.